2017
DOI: 10.1186/s13073-017-0491-4
|View full text |Cite
|
Sign up to set email alerts
|

A putative causal relationship between genetically determined female body shape and posttraumatic stress disorder

Abstract: BackgroundThe nature and underlying mechanisms of the observed increased vulnerability to posttraumatic stress disorder (PTSD) in women are unclear.MethodsWe investigated the genetic overlap of PTSD with anthropometric traits and reproductive behaviors and functions in women. The analysis was conducted using female-specific summary statistics from large genome-wide association studies (GWAS) and a cohort of 3577 European American women (966 PTSD cases and 2611 trauma-exposed controls). We applied a high-resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 53 publications
(52 reference statements)
2
35
0
Order By: Relevance
“…In contrast, negative r g with PTSD include subjective well-being, education, and a strong correlation with parents age at death (r g = -0.70). Significant positive correlations were also found for reproductive traits such as the number of children ever born, and, as previously reported for women, 26 PTSD was negatively correlated with age at first birth.…”
Section: Genetic Correlations Of Ptsd With Other Traits and Disorderssupporting
confidence: 85%
“…In contrast, negative r g with PTSD include subjective well-being, education, and a strong correlation with parents age at death (r g = -0.70). Significant positive correlations were also found for reproductive traits such as the number of children ever born, and, as previously reported for women, 26 PTSD was negatively correlated with age at first birth.…”
Section: Genetic Correlations Of Ptsd With Other Traits and Disorderssupporting
confidence: 85%
“…34 For the variants included in the instrumental variable, we performed LD clumping by excluding alleles that have R 2 ≥ 0.001 within a 10,000-kb window with another variant with a smaller association P-value. Since different MR methods have different sensitivities to different potential issues, accommodate different scenarios, and vary in their statistical efficiency, 15 we considered a range of MR methods. The primary analysis was conducted considering a random-effect inverse-variance weighted (IVW) method.…”
Section: Causal Inferencementioning
confidence: 99%
“…Large scale genome-wide association studies (GWAS) have now identified genetic variants that can be used to define reliable genetic instruments that can be applied for causal inference in a MR analysis. [14][15][16][17][18] The basic principle in MR is that genetic variants that either alter the level of, or mirror the biological effects of, a modifiable environmental exposure that itself alters disease risk should be related to disease risk to the extent predicted by their influence on exposure to the environmental risk factor. 19 Previous large-scale GWAS conducted by the Social Science Genetic Association Consortium (SSGAC) investigated traits related to educational attainment (e.g., number of years of schooling and most advanced math course ever successfully completed), identifying a number of loci and biological pathways regulating brain mechanisms at the basis of the human cognitive ability.…”
Section: Introductionmentioning
confidence: 99%
“…Mendelian randomization (MR) is a method that relies on genetic data to infer causal relationships, for example, between an exposure (e.g., a metabolite) and an outcome (e.g., psychiatric disorder) using genetic variants as instrumental variables (27)(28)(29)(30)(31). There are few studies evaluating the role of metabolites on phenotypes resulting from exposure to trauma and no study to date has examined the putative causality between these factors using the MR approach.…”
Section: Introductionmentioning
confidence: 99%